1992
DOI: 10.1093/bja/69.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Anticonvulsant Activity in Experimental Epileptic Status

Abstract: We have examined the anticonvulsant properties of propofol in high doses in two experimental models of status epilepticus: generalized pentylenetetrazol (PTZ)-induced seizures and partial, cortically applied penicillin G-induced seizures. Propofol was administered either as a single bolus injection or as a bolus injection followed by an infusion for 1 h. When administered as a single bolus injection, propofol 12 mg kg-1 suppressed electrical and clinical seizures in PTZ generalized epileptic status, and an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 14 publications
0
17
1
1
Order By: Relevance
“…The similar pharmacological properties of propofol (this study; Frenkel & Urban, 1991) suggest that an analogous mechanism underlies its Na+ channel blocking effects. Selective antagonism of repetitively active neurones may contribute to both the anticonvulsant (De Riu et al, 1992) and general anaesthetic properties of propofol. Inhibition of Na' channels in depolarized neurones would be expected to exert a neuroprotective effect (Urenjak & Obrenovitch, 1996), although results from studies of the neuroprotective properties of propofol have been inconsistent (Kochs et al, 1992;Ridenour et al, 1992;Amorim et al, 1995;Arcadi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The similar pharmacological properties of propofol (this study; Frenkel & Urban, 1991) suggest that an analogous mechanism underlies its Na+ channel blocking effects. Selective antagonism of repetitively active neurones may contribute to both the anticonvulsant (De Riu et al, 1992) and general anaesthetic properties of propofol. Inhibition of Na' channels in depolarized neurones would be expected to exert a neuroprotective effect (Urenjak & Obrenovitch, 1996), although results from studies of the neuroprotective properties of propofol have been inconsistent (Kochs et al, 1992;Ridenour et al, 1992;Amorim et al, 1995;Arcadi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on rabbits, propofol has been demonstrated to suppress epileptic discharges and it has clinically been shown to end seizures in seizure behaviors. In the mentioned study, the time to stop seizures by propofol is identified as 6 minutes and it is reported that seizures did not continue in the follow ups [35]. In another study that compares propofol with other benzodiazepines, it is reported that propofol acts fast, however, it causes relapses at a rate of 19-33%, and therefore, recurring doses might be useful regarding treatment [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to use, fast acting, and postinfusional recovery of consciousness is quick. There have been a number of favourable reports of its use in status epilepticus [40,41], and it has demonstrated some antiepileptic activity in animal seizure models [42]. It has, however, been reported to precipitate seizures [32] and in intra-operative recordings, it has activated epileptiform discharges on the electrocorticogram [33].…”
Section: Discussionmentioning
confidence: 99%